(untitled) (Communications in Computational Physics, 2007)
We investigate the structural and mechanical properties of single-walled carbon nanotubes (SWNTs) under hydrostatic pressure, using constant-pressure molecular dynamics (MD) simulations. We observed that all the SWNTs, independent of their size and chirality, behave like a classical elastic ring exhibiting a buckling transition transforming their cross-sectional shape from a circle to an ellipse. The simulated critical transition pressure agrees well with the prediction from continuum mechanics theory, even for the smallest SWNT with a radius of 0.4nm. Accompanying the buckling shape transition, there is a mechanical hardness transition, upon which the radial moduli of the SWNTs decrease by two orders of magnitude. Further increase of pressure will eventually lead to a second transition from an elliptical to a peanut shape. The ratio of the second shape transition pressure over the first one is found to be very close to a constant of ∼1.2, independent of the tube size and chirality.